2007
DOI: 10.1002/mc.20274
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Ras/Raf‐1/ERK actions in the magnolol‐induced upregulation of p21 and cell‐cycle arrest in colon cancer cells

Abstract: Previously, we showed that magnolol induces cell-cycle arrest in cultured colon and liver cancer cells through an upregulation of the p21 protein. The aim of this study was to delineate the molecular mechanism underlying this magnolol-induced increase of p21 protein. Thus our RT-PCR analysis demonstrated that the mRNA levels of p21 were increased at 1 h after magnolol treatment and sustained for at least 24 h. The p21 promoter activity was also increased by magnolol treatment. Western blot analysis demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…10 It is of interest that up-regulation of p21 CIP1/WAF1 mRNA but down-regulation of its protein after Fe depletion are different to the effects on its expression during cell-cycle arrest in response to other conditions. For instance, previous studies showed that p21 CIP1/WAF1 mRNA and protein were up-regulated during cellcycle arrest, [74][75][76][77] suggesting increased expression at the transcriptional and posttranscriptional levels. Moreover, in the current study, G 1 /S arrest induced by FCS starvation caused downregulation of both p21 CIP1/WAF1 mRNA and protein levels in MCF-7 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…10 It is of interest that up-regulation of p21 CIP1/WAF1 mRNA but down-regulation of its protein after Fe depletion are different to the effects on its expression during cell-cycle arrest in response to other conditions. For instance, previous studies showed that p21 CIP1/WAF1 mRNA and protein were up-regulated during cellcycle arrest, [74][75][76][77] suggesting increased expression at the transcriptional and posttranscriptional levels. Moreover, in the current study, G 1 /S arrest induced by FCS starvation caused downregulation of both p21 CIP1/WAF1 mRNA and protein levels in MCF-7 cells (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were transfected with 100 nM of CDKN1A (p21), NF-kB (p50 or 65) siRNA or non-specific siRNA (Bioneer, Co., Daejon, Korea) and p21 mutant plasmid (CDKN1A p21, obtained from Dr Anindya Dutta, Department of Biochemistry and Molecular Genetics, University of Virginia School of Medicine, Charlottesville, VA, USA), which has mutated cyclin D1/CDK4 complex binding site (Cy1 site, ᭝17-24) using WelFect-EX plus transfection reagent (WelGENE, Seoul, Korea) prepared in a serum-free culture medium at 37°C (Hsu et al, 2007). After 6 h, a complete medium was added and the cells were further cultured for 24 h.…”
Section: Transfection Of Sirna and P21 Mutant Plasmidmentioning
confidence: 99%
“…18,19) Several researchers have shown that magnolol inhibits proliferation and induces apoptosis in cancer cells by upregulating p21 cip/Waf1 , 20) inhibiting DNA synthesis, 21) activating the epidermal growth factor receptor (EGFR)/phosphoinositide 3-kinase (PI3K)/Akt signaling pathway, 18) as well as Ras/Raf-1/ Erk actions. 22) However, it remains to be determined whether Note * To whom correspondence should be addressed. e-mail: jykim@cnu.ac.kr…”
mentioning
confidence: 99%